COMPANIES CONDITION COMPARISON BASES ON THE INDICATORS OF CONSTANCY OF THE RATIO «PRICE/EARNINGS» - O. Zemlyanskiy (Publishing House of the State University of Management, 2017)
There offer a comparative analysis of the company condition based on the calculation of indicators of constancy ratio Z «Price/Earnings» acquiring and has been acquired companies or any company on the market, with company profits growth forecast.